Prevalence of Plasmodium falciparum plasmepsin2/3 gene duplication in Africa and Asia: a systematic review and meta-analysis - Karol J. Marwa; Manase Kilonzi; Rajabu Hussein Mnkugwe; Vito Baraka; Anthony Kapesa; Richard Mwaiswelo; Maria Zinga; Bruno P. Mmbando; John P. A. Lusingu; Erasmus Kamugisha (Malaria Journal)
Abstract Background The Plasmodium falciparum delayed clearance phenotype due to the emergence of partial artemisinin resistance has been documented in Asia and Africa, where it is associated with treatment failure of artemisinin-based combination therapy (ACT). The amplification of the Plasmodium falciparum plasmepsin2/3 gene (pfpm2/3) has been shown to decrease the susceptibility of P. falciparum to piperaquine, leading to treatment failure among patients on dihydroartemisinin-piperaquine. The present systematic meta-analysis summarises the evidence of pfpm2/3 gene amplification in Asia and Africa. Methods The protocol for the review was registered at the PROSPERO (Reference number: CRD42024599774). Thirty-four studies conducted in Africa and Asia, reporting pfpm2/3 gene amplification among P. falciparum isolates, were identified through the Medline, Google Scholar, Cochrane Central Register of Controlled Trials (CENTRAL), LILACS, and EMBASE online databases. The potential for publication bias was evaluated by examining asymmetry in funnel plots and using Egger’s test. Pooled proportions estimates were calculated using the random effects model, while heterogeneity was assessed through I2 statistics. Sub-group analysis was performed based on the year of sample collection and continent. Results The heterogeneity among the studies included in the meta-analysis was high (I2 > 95%, p < 0.01). The funnel plot was asymmetrical, suggesting that publication bias affected the meta-analysis. However, Egger’s test and Begg’s (adjusted to Kendall’s) scores for the pooled proportions of the pfpm2/3 gene confirmed no potential publication bias (p = 0.083 and 0.163, respectively). A total of 34 studies involving 4,005 P. falciparum isolates were included in this review. Of the 34 studies, 18 (53%) were conducted in Asia, and 16 (47%) were conducted in Africa. The samples for these studies were collected from 2009 to 2019. Among these studies, 15 (44%) were performed before 2016. The estimated pooled proportions of pfpm 2/3 gene amplification via the random effects model were 16.0% (95% CI 8.0–26.0%). Subgroup analysis (per continent and year of sample collection) revealed that the pooled proportions estimates of pfpm2/3 gene amplification were greater in Asia (25.0%, 95% CI 9.0–45.0%) than in Africa (8.0%, 95% CI 2.0–15.0%) and lower before 2016 than 2016 to 2020 (11%, 95% CI 3.0–23% and 19%, 95% CI 7.0–36%, respectively). Conclusion The present review provides up-to-date evidence on the pfpm2/3 gene amplification. A substantial pooled proportion of pfpm2/3 gene amplification was reported, and many of the amplifications were observed in isolates from Asia rather than Africa. This calls for further efforts to monitor/control the emergence and spread of partner drug resistance in the regions to avoid the emergence of total ACT resistance, which will compromise global efforts toward eliminating malaria.